The crustacean bycatch of seabob shrimp Xiphopenaeus kroyeri (Heller, 1862) fisheries in the Cananéia region, southern coast of São Paulo, Brazil - Bochini, Gabriel Lucas [UNESP]; Stanski, Gilson [UNESP]; Castilho, Antonio Leão [UNESP]; Costa, Rogerio Caetano da [UNESP] (Elsevier, 2019)
The bycatch of shrimp fisheries is highly diverse, but still understudied in the coast of Cananéia (São Paulo, Brazil), where shrimp fisheries are very intensive. Aiming to fill this gap, we analysed the diversity of crustaceans in the bycatch of seabob shrimp (Xiphopenaeus kroyeri) fisheries. Samplings were taken monthly, from March 2013 to May 2014, using a shrimp bottom trawling net aboard a commercial vessel. The crustacean bycatch encompassed 22 families, 36 genera and 46 species. The families with the highest species richness were Portunidae (8 species) and Penaeidae (5 species), corresponding to 17.4% and 10.9%, respectively, of all species caught. Overall, the abundance of X. kroyeri was higher than that of the crustacean bycatch except during in December 2013-February 2014, when the ratio was nearly 1:1 (Binomial test, p <0.05). There was a great variation in the abundance of crustaceans throughout the year, and the highest proportion of bycatch occurred outside the period when the fishery is forbidden. We provide evidence that the trawling in Cananéia captures a great diversity of crustaceans that coexist with the target shrimp species.
Keywords: Crustacean; Decapoda; Habitat sharing; Impact of trawling fisheries